Asymmetry of the nasofacial skull in toothed whales (Odontoceti) - Huggenberger, S.; Leidenberger, S.; Oelschlaeger, H. H. A. (WILEY, 2017)
In this study, the nasal asymmetry of odontocetes (toothed whales) was analyzed morphometrically by placing landmarks on photographed nasofacial skulls from 12 different species and genera that belong to four odontocete families. The results show that the degree of asymmetry tends to be linked with the mechanism of click sound generation in odontocetes. The narrow-banded high-frequency echolocators, such as Phocoenidae, Inia geoffrensis, Pontoporia blainvillei and Cephalorhynchus commersonii, show a more symmetric skull than the broad-banded low-frequency species (most delphinids). Exceptions to this tendency are, for example Kogia sima, with narrow-banded high-frequency clicks and a high degree of nasofacial asymmetry, and Feresa attenuata, a delphinid with broad-banded low-frequency clicks and a moderate degree of nasofacial asymmetry. Accordingly, there is no consistent functional correlation between click type and skull asymmetry probably because the nasofacial skull does not strictly reflect the anatomy of the sound generating nasal soft structures.